Experimental analysis and improvement of the DC method for self-heating estimation. (September 2019) - Mori, C.A.B.; Agopian, P.G.D.; Martino, J.A.
Abstract: This paper reports an improved method for estimating the thermal resistance of a MOSFET device using the inverse of the transistor efficiency as a function of the power applied to the transistor's channel. This method was deduced considering that the main effect of the self-heating is on the carriers' mobility, where the temperature dependency, vertical/lateral field degradation and saturation velocity were taken into account. After performing the analytical considerations, the method was validated through numerical simulations to verify if its results were compatible with other traditional pulsed-like method for the thermal resistance extraction. This improved method was applied experimentally to attest its robustness. The advantages of this method are the use of DC measurements only and differences smaller than 10 K in the estimation of the absolute channel temperature due to the self-heating effect compared to a traditional pulsed-like method for the UTBB SOI studied in this work.